Phenothiazine antipsychotics exhibit dual properties in pseudo-allergic reactions: Activating MRGPRX2 and inhibiting the H1 receptor. (July 2019) - Hou, Yajing; Che, Delu; Wei, Di; Wang, Cheng; Xie, Yitong; Zhang, Kaining; Cao, Jiao; Fu, Jia; Zhou, Nan; He, Huaizhen
Highlights: Phenothiazine antipsychotics activate calcium mobilization and induce degranulation in mast cells. Phenothiazine antipsychotics increase serum histamine via Mrgprb2 without Evans blue extravasation or paw swell. Phenothiazine antipsychotics could interact with H1R and exhibit as antagonists. MRGPRX2 is essential for the degranulation of mast cells triggered by phenothiazine antipsychotics. Dual properties of phenothiazine antipsychotics in pseudo-allergic reactions rely on structural specificity. Abstract: Phenothiazines are a class of antipsychotics that share the same tricyclic structure and are widely used in clinical settings. Adverse reactions from these drugs, however, have been regularly reported, with allergic skin reactions noted in some cases. Nevertheless, the mechanisms underlying anaphylaxis by these drugs have not been described. In the present study, we found that phenothiazine antipsychotics increased calcium mobilization and activated mast cells to release β -hexosaminidase, histamine, and tumor necrosis factor-α via Mas-related G-protein-coupled receptor member X2 (MRGPRX2) in vitro. In addition, they induced histamine release in serum via Mrgprb2 in C57BL/6 mice without Evans blue extravasation or paw swell. Further experiments indicated these drugs had good interaction with the histamine H1 receptor (H1R) and show an anti-calcium mobilization effect on H1 R-HEK293 cells, which confirmed a potential antagonist effect of these drugs on the H1 R. The molecular docking and activity experiments indicated that the N-methyl substitution on the side chain of these drugs played a significant role in activating MRGPRX2, while the phenothiazine tricyclic ring was associated with the inhibiting effect on the H1 R. Therefore, due to their dual properties of increasing histamine levels without obvious allergic symptoms, clinicians should be highly vigilant for damage from histamine accumulation and long-term inflammatory reactions during the clinical use of phenothiazine antipsychotics.